2022
DOI: 10.1001/jamanetworkopen.2021.45934
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adjuvant Hormone Therapy Timing With Overall Survival Among Patients With Hormone Receptor–Positive Human Epidermal Growth Factor Receptor-2–Negative Early Breast Cancer Without Chemotherapy

Abstract: IMPORTANCEStudies have shown that delayed initiation of surgery and adjuvant chemotherapy is associated with lower rates of breast cancer survival. However, it remains unclear whether delayed initiation of adjuvant hormone therapy (AHT) is associated with survival. OBJECTIVE To assess the association of time to adjuvant hormone therapy (TTH) with breast cancer survival and evaluate the factors associated with AHT. DESIGN, SETTING, AND PARTICIPANTS This cohort study examined data from the National Cancer Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In addition to disparities in use of and response to ODX results, women with HR+/HER2breast cancer are eligible for endocrine therapy as part of their treatment regimens. Delays in the initiation of endocrine therapy have been associated with decreased survival: in a study of 144,103 women, Fu et al found that time to adjuvant hormone therapy of >150 days was associated with decreased survival (HR 1.31, 95% CI 1.26-1.35) [59]. Within this study, Black women were at increased risk for initiating endocrine therapy >150 days (OR 1.66, 95% CI 1.55-1.77).…”
Section: Endocrine Therapymentioning
confidence: 99%
“…In addition to disparities in use of and response to ODX results, women with HR+/HER2breast cancer are eligible for endocrine therapy as part of their treatment regimens. Delays in the initiation of endocrine therapy have been associated with decreased survival: in a study of 144,103 women, Fu et al found that time to adjuvant hormone therapy of >150 days was associated with decreased survival (HR 1.31, 95% CI 1.26-1.35) [59]. Within this study, Black women were at increased risk for initiating endocrine therapy >150 days (OR 1.66, 95% CI 1.55-1.77).…”
Section: Endocrine Therapymentioning
confidence: 99%
“… 12 , 13 Of the nearly 300 000 women diagnosed with breast cancer annually, about 83% have hormone receptor–positive tumors, which makes them eligible for adjuvant hormone therapy that is associated with increased survival and decreased risk of recurrence. 33 Yet prior studies associated Medicaid insurance with lower use of both radiation and hormone therapy compared with other insurance. 12 , 13 , 18 Using registry data alone, our findings confirmed these reported disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in breast cancer surgery is a topic receiving national attention in the US, given that some prior studies have observed worse survival outcomes with longer times from breast cancer diagnosis to surgical treatment . However, the specific time point after which it is disadvantageous to have surgery is unknown.…”
Section: Introductionmentioning
confidence: 99%